Ways to improve the performance of students in the Kingdom of Saudi Arabia in the results of international tests (PISA) from the point of view of educational supervisors - Al-Subhi, Afaf Othman; Al-Subhi, Wafiah Othman; Al-Tamam, Abdullah Ali (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the reasons for the poor performance of Saudi students in the results of the international PISA tests and ways to improve them from the point of view of educational supervisors in Yanbu city, and to present proposals to improve the level of performance of Saudi students in the results of the international PISA tests for mathematics, science and reading from the point of view of educational supervisors, as well as to reveal the nature of the differences in the responses of sample members about the reasons for the poor performance level of Saudi students in the international PISA tests for mathematics, science and reading attributed to the variables (qualification - experience). The study followed the descriptive analytical approach, and the questionnaire as a tool was distributed to a purposive sample of (134) supervisors. The study relied on the questionnaire as a tool for collecting data and applied to the supervisors. The study reached many results, the most important of which are: that the reasons for the poor performance level of Saudi students in the international PISA tests came at an average of (4.01) with a degree of (large), and the necessary proposals to improve the level of students’ performance in the results of the international tests (PISA) received an average of (4.62) with a rating of (very large), and showed that there were no differences in the responses of sample members about the reasons for the weakness The level of students’ performance in international tests is attributed to the variables (qualification - experience). Based on the results, the study recommended the necessity of inviting the responsible authorities in the Ministry of Education in the Kingdom to benefit from the proposals presented by the current study and translate them into practical procedures within their treatment and development plans to raise the level of students’ performance in the results of international tests (PISA) during future participation.